Critical Evaluation of Governance and Good Corporate Governance in Managing Mudharabah Deposits at Bank Aceh - Muhammad Agmar Media; Marzuki Marzuki; Teuku Yasman Saputra; Mukhsin Nuzula (Universitas Muhammadiyah Makassar, 2025)
The management of mudharabah deposits at Bank Aceh Syariah presents governance challenges arising from limited coordination among the Board of Commissioners, the Board of Directors, and the Sharia Supervisory Board. This study investigates how these governance organs perform their supervisory, operational, and sharia compliance roles in managing deposit funds. Unlike previous studies that focus mainly on structural aspects of governance, this research highlights the practical gaps that emerge when strategic decision-making is dominated by a single governance organ. Using a qualitative approach, data were collected through interviews, observations, and document reviews. The findings show that although the governance structure appears adequate, its implementation is hindered by restricted information flow, the Directors’ dominance in strategic decisions, and the Sharia Supervisory Board’s limited substantive involvement. These insights provide a novel contribution by illustrating how governance dynamics directly shape intermediation effectiveness and sharia compliance. The study concludes that a more integrated governance framework is essential to strengthen accountability, enhance sharia alignment, and support regional economic development